Konteksty i implikacje III Sesji Plenarnej „Der synodale Weg” we Frankfurcie nad Menem, 3–5.02.2022 roku - Grzegorz Chojnacki (Studia Paradyskie, 2022)
The Third Plenary Session of “Der Synodale Weg” and the three documents adopted during it allow for a preliminary diagnosis of the renewal and reform process in the Catholic Church in Germany started in 2019. This diagnosis shows that members of the Church community are concerned about the increasing number of apostasies and difficulties in regaining trust and credibility caused by the abuse of authority and power in many dimensions of spiritual and physical (sexual) life. Adopted documents in the theological dimension revise the precedence of theological sources, placing greater emphasis on the “signs of the times” as a locus theologicus and emphasising the greater importance of the Episcopal conference of a given country for decisions within authentic teaching in the Universal Church. Also the assembly of “Der Synodaler Weg” and the synodal councils to be constituted at the diocesan level should be not only advisory but also decisive. Such reforms of the Catholic Church meet with movements contesting such decisions, indicating that the participants of this assembly do not have the mandate to oblige believers in Germany to obey them. The Holy See issued a Declaration, pointing out that the decisions made by the assembly of “Der Synodale Weg” are not binding, neither in the case of proposed new forms of Church governance, nor in matters of faith and morals.